FSG01: Online interview with young Ivorian woman without children about sex education and school pregnancies (Health Discourses as Moral Communication? Linguistic Case Studies from Côte d'Ivoire and Cameroon, 2020)
Online interview with young Ivorian woman without children about sex education and school pregnancies.
Keywords: Communication; Ethics; Women; Pregnancy; Reproductive health; Africa; Teenage pregnancy; Abortion; Contraception; Prevention; Applied ethics; Birth Control; Moral Communication; Côte d'Ivoire; Ivory Coast; Adolescent Pregnancy; Morality